Proton mobility for the description of dynamic aspects of freeze-dried fruits - Agudelo Laverde, Lina Marcela (2013)
The partitioning of water sorption isotherms into different zones, according to the strength of water interactions with solids has very important practical applications. However, the dynamic properties of water play an important role in complementing the information provided by water sorption isotherms. One of the most successful techniques used to prove the dynamic behavior of water in foods systems is pulsed NMR. The aim of this study was to apply the concept of proton mobility in order to better define the water-related dynamic aspects of freeze-dried fruits. Different water mobility populations were defined through 1H NMR transversal relaxation times, obtained after the application of several pulses sequences. The water content limits at which proton populations with different mobility appeared, allowed a more complete and precise description of water behavior at the different sorption stages than the parameters obtained by the application of sorption mathematical models.